145 What outcomes are important in a drug trial for chronic breathlessness and are we capturing change?. Issue Volume 9: Issue (2019)Supplement 1 (March 2019) - Lovell, N; Etkind, SN; Bajwah, S; Maddocks, M; Higginson, IJ
Abstract : Background: Chronic breathlessness is common, distressing and remains a challenging to assess and treat. New treatments are emerging, but must be evaluated using appropriate outcomes that reflect the concerns of people experiencing the symptom. Aim: To determine which outcomes are important to patients with chronic breathlessness, and the ability of outcome measurement tools to capture change during a drug treatment trial. Methods: Mixed-methods analysis of a multi-centre randomised double-blind feasibility trial of mirtazapine (ISRCTN registration 33236160). Quantitative outcome measures: numerical rating scale (NRS) for worst breathlessness in the last 24 hours, and chronic respiratory questionnaire (CRQ) were paired to in-depth qualitative data from interviews exploring outcomes of importance within the trial. Qualitative data was analysed thematically and quantitative data analysed according to the standard guidance for each questionnaire. The combined analyses were then triangulated, drawing upon a model of total breathlessness. Results: Paired data were available for 22 of 64 participants in the trial (data collected August 2016-December 2017). 16/22 (73%) were male; median (range) age 72 (57–85) years. Primary diagnoses were chronic obstructive pulmonary disease 10/22 (45%), interstitial lung disease 9/22 (41%), chronic heart failure 2/22 (9%) and lung cancer 1/22 (4%). Participants described outcomes of importance encompassing physical, social, emotional and spiritual domains. For many, perceived changes described during qualitative interview were consistent with changes in both NRS and CRQ scores. This was despite some participants expressing difficulties aligning an experience of breathlessness when completing scale for scale-based questionnaires. Conclusions: The main concerns described by participants in a drug trial for chronic breathlessness cross multiple health domains supporting a model of total breathlessness and the inclusion of multi-domain measures within trials. The agreement between paired qualitative and quantitative data indicates that both the NRS and CRQ outcome measures capture changes described by participants appropriately, and are suitable to use in definitive trials.